Knowledge, attitudes and practices (KAP) regarding COVID-19 management among indigenous people in Bangladesh - N. M. Refat Nasher; Ashraf-Un-Naher (National Geographical Journal of India, 2023)
The knowledge, attitudes, and practices (KAP) substantially affect public responsiveness and understanding of disease origin, transmission, and regulator in a health emergency. Concerning COVID-19 safeguard practices in Bangladesh, this study intended to identify KAP among indigenous individuals and the determinants of those behaviours. To investigate underlying factors cross-sectional face-to-face questionnaires survey was conducted from April to May 2022 among 163 indigenous people from remote areas of Bangladesh. The respondents (45 % male and 55% female) are between 18 to 85 years. In addition to socio-demography, information on knowledge, attitudes, and behaviour is acquired. The student t-test and ANOVA are used to find the mean KAP score and other variables. About 75 per cent of participants had positive views on COVID-19 management, and the knowledge questionnaire had a total accuracy rate of 74.7 per cent. Despite the vaccination rate of 84%, the practice was poor (26.4%). Fewer respondents (9.8%) used face masks, and just 4 per cent washed their hands properly. The sociodemographic variables had less control over COVID-19 knowledge, except education. Higher education is significant for COVID-19 knowledge (β = 0.36. P < 0.01). The hierarchical regression model found hand protection insignificant. Males with higher educational degrees, unmarried, and those who made more money per hour had much higher KAP scores.